Issues of lean-agile software development environment - Kumar Nath, Udit; Mahapatra, Satyasundara; Pattnaik, Prasant Kumar; Jagadev, Alok Kumar (International Journal of Engineering and Technology, 2018)
The popular waterfall model is widely accepted approach for project management paradigm; however lean based agile model is the recent revolution to reduce work in progress items and makes transformation to better process by identifying and eliminating non-value-add activities and increase productivity with quality of deliverables. This paper includes the issues that involved in lean- agile process.